Pengujian Performa Payload Video UAV untuk Persiapan Implementasi pemantauan Kapal Illegal Fishing - Sunar Sunar; Ari Sugeng Budiyanta (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
The Aeronautics Technology Center of LAPAN develops a maritime surveillance system (MSS) based on an unmanned aerial vehicle (UAV) application, specifically to support the handling of illegal fishing vessels. This article discusses video payload testing. The test was carried out in the coastal area, Pamengpeuk, Garut, Indonesia on August 31, 2019. This place was chosen to simulate conditions with wind speeds that are similar to operating conditions in the marine environment during the actual implementation of the operation. The payload used has a video recording feature with the ability to zoom-in, zoom-out and locking-target-positions. UAVs fly loiter at an altitude of 300 m - 500 m above sea level while doing video recording and transmitted in real time to the Ground Control Station (GCS). The test results show the payload shows the zoom-in, zoom-out and locking target position features can operate properly. This feature is very useful to meet the needs of illegal fishing operations in the maritime survey system.